UJI AKTIVITAS DAN IDENTIFIKASI JAMUR RHIZOSFER PADA TANAH PERAKARAN TANAMAN PISANG (Musa paradisiaca) TERHADAP JAMUR FUSARIUM - Dewi Nur Anggraeni; Muhammad Usman (Universitas Medan Area, 2015)
The main cause of decline in banana production is fusarium wilt caused by the fungus Fusarium oxysporum f.sp.cubense (Foc). This disease is systemic, it is very dangerous because it can kill plants. Fusarium wilt disease ranks first in the list of diseases of bananas in Indonesia, fusarium wilt very difficult to control because it has not found a commercial banana cultivars resistant. Integrated Pest Management (Biological Control) using biological agents, one of which is the rhizosphere that has the ability to suppress the growth of Fusarium wilt (Fusarium oxysporumf.sp.cubense) in vitro. The purpose of this study was to determine the ability of an antagonist of the rhizosphere fungus to fungus fusarium. This research method is a rhizosphere fungal activity test against fusarium fungus. The results showed that 12 isolates the rhizosphere has the potential to inhibit the growth of fungi fusarium the percentage inhibition ie 82% of isolates A1, B2 D3 by 83% and 80%, A2 isolates the isolates that produce inhibition of the smallest amounting to 15%. Based on identification consists of rhizosphere fungi genus Trichoderma sp., Aspergillus sp., And Penicillium sp.